Foreign Language Development During Temporary School Closures in the 2020 Covid-19 Pandemic - Hopp, Holger; Thoma, Dieter (Frontiers in Education, 2020)
This report assesses effects of temporary school closures during the 2020 Covid-19 pandemic in Germany on early foreign language development among primary-school learners of English. We analyze English vocabulary and grammar skills before and after fifteen weeks of school closures and the subsequent suspension of foreign-language (FL) instruction. In addition, we compare data from 141 students who experienced interruptions in schooling in 2020 to a matched group of 128 students who had received continuous instruction in the previous school year. The study did not find any negative effects of instructional suspension on FL vocabulary or grammar. Moreover, variance between students did not increase, and the effect structure of cognitive predictors of FL skills remained the same. Overall, temporary suspensions of FL instruction of the nature and length experienced during the 2020 Covid-19 pandemic did not appear to have detrimental effects on general foreign language learning among young students.